PENGARUH MOTIVASI, PELATIHAN DAN KOMPETENSI TERHADAP PENGEMBANGAN KARIR KARYAWAN BANK - Aryansuka Mautama Putra, I Putu Galing; Mujiati, Ni Wayan (Buletin Studi Ekonomi, 2022)
Employees are a very valuable asset for an organization or company. So many companies take care of their employees by providing career development as a form of positive support. Through this study, it was found that there were problems related to employee career development at a bank in Bali Province. This study aims to analyze the effect of employee motivation, training, and competence at the bank. The research location is one of the banks in Bali Province with a total of 60 employees. The sampling technique was carried out by saturated sampling. Data was collected by interview and using a questionnaire. The data analysis technique in this research is multiple linear regression analysis. The results showed that motivation, training, and competence had a positive and significant effect on career development. The implications of this research theoretically support the findings of previous research as well as studies related to career theory leading to the development of interests and self-concept, resulting from the ability to make choices. The practical implication for banks is related to employee career development, it is necessary to pay attention to the motivation, training and competence aspects of employees.